Knowledge, Attitude and Practice of Medical Ethics among Doctors and Nurses in Pokhara Valley, Nepal - Hirachan, N.; Shrestha, N. (Kathmandu University Medical Journal, 2022)
Background Medical ethics is defined as the ethical obligations of medical professionals towards their patients, colleagues, and society. The inadequacy and non-uniformity of this topic has been associated with rising cases of professional misconduct and medical negligence all over the world. Objective To assess and compare the status of knowledge, attitude and practice of medical ethics among medical doctors and nurses in three major hospitals of Pokhara valley. Method This was a cross-sectional study conducted from 15th Mar 2018 to 13th Apr 2018; in which 124 doctors and 103 nurses were asked to fill up medical ethics related questionnaire. The data was entered in SPSS file and the association of variables was determined by Chi-square and statistical significance was considered if the p-value < 0.05. Result The study showed that 56.5%, 8.1%, and 13.7% of doctors were aware of the Hippocratic oath, Nuremberg Code, and Helsinki declaration respectively compared to only 1% of nurses. There was a significant difference in opinions on various questions related to medical ethics with p-value < 0.05 in 12 out of 22 questions. Only a few (12.1% doctors vs. 25.2% nurses) stood in support of the physician-assisted dying. Conclusion The study showed that there was inadequate as well as a non-uniform level of knowledge of three major codes of medical ethics and principles related to it which resulted in significant disparity in the attitude and practice of medical ethics among doctors and nurses in Pokhara valley.